Intratympanic steroid injection as a first-line therapy in uremia patients with sudden sensorineural hearing loss. (August 2015) - Tsai, Hsun-Tien; Hsueh, Naiwei; Huang, Chih-Ming; Lin, Hung-Ching
Abstract Conclusions: ITSI as a first-line therapy in uremia patients with SSNHL offers a valid and safe treatment compared with intravenous systemic steroid treatment. A specific pathophysiology caused by possible sodium pump paralysis may be explained for uremia patients with SSNHL. Objective: To compare the efficacy of intratympanic steroid injection (ITSI) with that of systemic intravenous steroids as a first-line therapy in uremia patients with sudden sensorineural hearing loss (SSNHL). Materials and methods: A total of 23 consecutive uremia patients with SSNHL were enrolled in this study. Patients were divided into two groups: the ITSI group (n = 15) and the non-ITSI group (n = 8), in which patients received intravenous systemic steroid treatment. The two groups were homogeneous in all respects. Results: The hearing improvement and relative gain were statistically significant between the two groups. The value of hearing gain (ΔPTA = PTA pre – PTA post) in the ITSI group and the non-ITSI group was 24.6 ± 16.4dB and 8.4 ± 19.3dB. The value of relative gain (ΔPTA/PTApre) in the ITIS group and the non-ITSI group was 31.1 ± 22% and 9.4 ± 20.5%. In the ITSI group, 11 patients (73.3%) exhibited hearing recovery (ΔPTA > 10 dB).